Promoting vaccine acceptance in college students: an analysis of the KSRE Health Communication Vaccine Confidence Campaign - Aggarwal, Janvi (Kansas State University, 2024)
In the United States, widespread acceptance, and utilization of vaccines among adults presents a significant opportunity for improving public health. However, vaccine hesitancy remains a substantial challenge, driven by factors such as misinformation, fear, safety concerns, and religious objections. This hesitancy poses serious risks, including increased susceptibility, potential disease transmission, and strain on healthcare systems. Addressing these issues necessitates effective education, transparent communication, and trust-building within vaccination programs. This report offers a comprehensive analysis of the Health Communication Vaccine Confidence Project, initiated at Kansas State University by Kansas State Research and Extension. It provides detailed information on the project's goals, approaches, and results. This approach aligns with the principles of Social Cognitive Theory, which emphasize the role of observational learning, social influence, and self-efficacy in shaping health-related behaviors. The study suggested a comprehensive framework for public health initiatives, emphasizing tailored messaging, credible spokespeople, and diverse university communication channels to enhance vaccination awareness among students.
Keywords: Vaccination; Hesitancy; University students; Immunization